Extracellular Vesicles & Co.: scaring immune cells in the TME since ever - Rodolfo, Carlo; Campello, Silvia (Frontiers in Immunology, 2024)
The health tissue surrounding a solid tumor, namely the tumor microenvironment (TME), is an extremely complex universe of cells, extracellular matrix, and signals of various nature, that support and protect the growth of cancer cells. The interactions taking place between cancer cells and the TME are crucial not only for tumor growth, invasion, and metastasis but they also play a key role in modulating immune system responses to cancer, and vice-versa. Indeed, tumor-infiltrating immune cells (e.g., T lymphocytes and natural killers) activity is greatly affected by signals (mostly ligands/receptors and paracrine) they receive in the TME, which frequently generate an immunosuppressive milieu. In the last years, it has become evident that soluble and receptor signaling is not the only way of communication between cells in the TME, with extracellular vesicles, such as exosomes, playing a central role. Among the different new kind of vesicles recently discovered, migrasomes look like to be of extreme interest as they are not only different from the others, but also have been reported as able to deliver a very heterogeneous kind of messages, able to profoundly affect recipient cells’ behavior. Indeed, the role played by the different classes of extracellular vesicles, especially in the TME, relies on their not-directional diffusion from the originating cells, while migrasomes released from migrating cells do have a directional effect. Migrasomes biology and their involvement in cancer progression, dissemination, and resistance to therapy is still a largely obscure field, but with promising development foreseen in the next future.